Profil hasil pemeriksaan CT-Scan pada pasien karsinoma nasofaring di Bagian/SMF Radiologi FK Unsrat RSUP Prof. Dr. R. D. Kandou Manado periode April 2015 â€“ Agustus 2016 - Ruslim, Matthew N.; Ali, Ramli H.; Loho, Elvie (e-CliniC, 2016)
Abstract: Nasopharyngeal carcinoma is the most common malignancy of the head and neck. In Indonesia, the prevalence is 6/100.000 and Manado has become one of the regions with the highest incidence of nasopharyngeal carcinoma. CT Scan imaging is a standard radiologic modality in diagnosing and evaluating nasopharyngeal carcinoma. This study was aimed to obtain the profile of CT Scan imaging in nasopharyngeal carcinoma patients. This was a retrospective descriptive study conducted in October 2016. Data were obtained from head and neck CT Scan request form and eventually there were 46 patients (63%) with the radiologic diagnosis of tumor mass in the nasopharynx. The majority of patients were males (30 patients; 65,2%); age group 50-59 years old (17 patients; 37%); and T4 as the size of the primary tumor (18 cases; 39.1%). There were five anatomical structures most frequently infiltrated, as follows: nasal cavity (39.1%), ethmoidal sinuses (30.4%), maxillary sinuses (23.9%), sphenoidal sinuses (23.,9%), and intracranial areas (19.6%).Keywords: nasopharyngeal carcinoma, computerized tomography scan.Â Abstrak: Karsinoma nasofaring merupakan keganasan kepala dan leher yang paling sering terjadi. Indonesia memiliki prevalensi sekitar 6/100.000 dan Manado menjadi salah satu daerah dengan insidensi karsinoma nasofaring yang tinggi. Pemeriksaan radiologi CT Scan, merupakan modalitas radiologis standar dalam mendiagnosis dan mengevaluasi karsinoma nasofaring. Penelitian ini bertujuan untuk mendapatkan profil pemeriksaan CT Scan pada pasien karsinoma nasofaring. Jenis penelitian ialah deskriptif retrospektif yang dilakukan pada bulan November 2016. Data diperoleh melalui lembaran permintaan pemeriksaan CT Scan kepala-leher dan didapatkan sebanyak 46 pasien (63%) dengan diagnosis radiologis massa tumor di nasofaring. Mayoritas pasien ialah ialah laki-laki berjumlah 30 pasien (65,2%), kelompok usia 50-59 tahun berjumlah 17 pasien (37%), dan ukuran tumor primer T4, pada 18 pasien (39,1%). Didapatkan lima struktur anatomi yang paling sering diinfiltrasi, yaitu kavum nasi (39,1%), sinus etmoidalis (30,4%), sinus maksilaris (23,9%), sinus sfenoidalis (23,9%), dan area intrakranial (19,6%). Kata kunci: karsinoma nasofaring, computerized tomography scan